Deodorizing printed layer for packaging bag
By using a combination of nanozel stone and a resin with transition metal on the packaging bag, an efficient deodorization printing layer is formed, which solves the problems of complex manufacturing process and inflexible deodorization layer in the prior art, and achieves efficient deodorization and good adhesion effects.
Patent Information
- Application Number
- JP2023150446
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-15
- Publication Date
- 2025-03-28
AI Technical Summary
When the prior art provides the deodorization function for packaging bags, the manufacturing process is complicated and the deodorization layer is not flexible enough. The large granule agent used causes rough printing layer and poor adhesion, which affects the appearance and function of the packaging bag.
Nanozeolites and resins with transition metals are used to form an efficient deodorizing printing layer. Nanazelite has high hydrophilicity and extended pore size, and can effectively adsorb odor molecules such as sulfides, and transition metals further improve adsorption performance.
The efficient deodorization performance and good smoothness of the deodorization printing layer are achieved, which improves the appearance and adhesion of the packaging bag, simplifies the manufacturing process, and improves the flexibility of the deodorization layer.
Smart Images

Figure 2025043118000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an odor eliminating printed layer for use in a packaging bag. [Background technology]
[0002] Foodstuffs, medicines, medical instruments, etc. may be subjected to heat sterilization treatment while sealed in a packaging bag. Also, foodstuffs may be cooked by heating while sealed in a packaging bag before being consumed.
[0003] When the contents are heated while sealed in a packaging bag, the contents themselves, the packaging material, or both may emit an unpleasant odor. The source of the unpleasant odor is thought to be denatured substances such as hydrocarbons, oils and fats, and proteins. Among these unpleasant odors, the protein denaturation odor, and especially the sulfur odor (the odor caused by sulfur compounds), are often problematic.
[0004] Furthermore, in the case of medicines, supplements, etc., the unpleasant odor inherent to the substances themselves can be a problem even if they are not heated.
[0005] In an attempt to absorb and eliminate such unpleasant odors, various packaging bag materials including a deodorant layer have been proposed in the prior art.
[0006] For example, Patent Document 1 describes a laminate for heat sterilization treatment, which includes a base layer and a sealant layer, and contains hydrophobic zeolite in the sealant layer. It explains that in this laminate, the hydrophobic zeolite in the sealant layer exerts an adsorption effect on odorous components.
[0007] Patent Document 2 describes a method for producing a packaging bag, which includes a step of providing a coating layer containing a zinc compound as a deodorant on the surface of an oxygen gas barrier material, arranging the coating layer on the content side of the oxygen gas barrier layer, and packaging the content. Patent Document 3 describes a gravure ink composition for adsorbing sulfur-based compounds, which contains zinc oxide, and applying the composition to a packaging bag to form a sulfur-based compound adsorption layer. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2019-177518 A [Patent Document 2] JP 2015-027892 A [Patent Document 3] Patent Publication No. 2022-099681 Summary of the Invention [Problem to be solved by the invention]
[0009] As in Patent Document 1, imparting a deodorizing function to any of the layers constituting the laminate for packaging bags is considered to be an effective means for adsorbing and removing unpleasant odors. However, this method requires kneading a deodorizing agent into a resin to produce a deodorizing film. Therefore, packaging bags containing deodorizing films have a complicated manufacturing process, and the deodorizing film produced lacks versatility.
[0010] In contrast, as in Patent Documents 2 and 3, a method in which an ink containing a deodorant is prepared and a deodorant layer is formed by a printing method using the ink is simple and the ink is highly versatile.
[0011] In addition, deodorants applicable to packaging bags are generally commercially available as large particle diameter particles, and therefore inks containing commercially available deodorants have insufficient printing characteristics, and the deodorant printed layer formed has poor smoothness, which leads to poor adhesion with other layers and poor appearance of the packaging bag.
[0012] Therefore, an object of the present invention is to provide a deodorizing printed layer having excellent deodorizing properties and smoothness, and a laminate for packaging bags including said deodorizing printed layer. [Means for solving the problem]
[0013] The present invention is as follows.
[0014] Aspect 1: A method for producing a composition comprising a nano-zeolite doped with a transition metal and a resin, Coating weight: 15.0g / m 2 Below is the Deodorizing printing layer for packaging bags. <<Aspect 2>> The deodorizing printed layer described in Aspect 1, wherein the average particle size of the nano zeolite is 5 nm or more and 500 nm or less. <<Aspect 3>> An odor-eliminating printed layer described in Aspect 1, wherein the SAR of the nano zeolite is 20 or less. Aspect 4: An odor-eliminating printed layer according to aspect 2, wherein the SAR of the nano zeolite is 20 or less. Aspect 5: The deodorizing printed layer according to aspect 1, wherein the transition metal is one or more selected from Ag, Cu, and Zn. <<Aspect 6>> The deodorizing printed layer described in Aspect 1, wherein the resin is one or more selected from urethane resin, (meth)acrylic resin, polyamide resin, nitrocellulose resin, chlorinated polyolefin resin, and vinyl chloride-vinyl acetate copolymer resin. <Embodiment 7> An ink for forming an odor-eliminating printing layer, comprising a nanozeolite doped with a transition metal and a resin. Aspect 8: The ink for forming a deodorant printed layer according to aspect 7, which is used to form the deodorant printed layer according to aspect 1. Aspect 9: A laminate for a packaging bag, comprising a base layer, the deodorizing printed layer described in aspect 1, and a sealant layer. Aspect 10: The packaging bag laminate of Aspect 9, further comprising one or two layers selected from a barrier layer and a reinforcing layer. Aspect 11: A method for producing the packaging bag laminate according to aspect 9, comprising: printing the ink according to claim 7 onto at least one of the substrate layer and the sealant layer; A method for manufacturing a laminate for a packaging bag. Aspect 12: A method for producing the packaging bag laminate according to aspect 10, comprising: printing the ink of claim 7 onto at least one of the substrate layer, the barrier layer, the reinforcing layer, and the sealant layer. A method for manufacturing a laminate for a packaging bag. Effect of the Invention
[0015] According to the present invention, there are provided a deodorizing printed layer having excellent deodorizing properties and smoothness, and a laminate for a packaging bag including said deodorizing printed layer. [Brief description of the drawings]
[0016] [Figure 1] 1 is a schematic cross-sectional view showing an example of an embodiment of the packaging bag laminate of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing one example of another embodiment of the packaging bag laminate of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Deodorizing printed layer for packaging bags The deodorant printed layer for packaging bags of the present invention contains nano zeolite doped with a transition metal and a resin, and has a coating weight of 15.0 g / m 2 The following is the result.
[0018] In the present invention, a nano-zeolite doped with a transition metal is used as a deodorant.
[0019] Zeolite doped with transition metals has a high affinity with polar compounds and has an expanded pore size, so it has excellent adsorption properties for sulfur compounds, for example. In addition, since it is nano-zeolite with a small particle size, the deodorant printed layer containing it has excellent smoothness. Due to these factors, the deodorant printed layer for packaging bags of the present invention functions as a deodorant layer that is particularly excellent in adsorption properties for sulfur compounds, even though it is a thin layer.
[0020] In addition, since the deodorant printed layer of the present invention has excellent smoothness, the occurrence of defective appearance is suppressed, and when formed into a laminate for packaging bags, it has the advantage of having excellent adhesion to other layers.
[0021] Furthermore, the deodorant printed layer of the present invention contains nano zeolite with a small particle size, and is a thin layer with excellent smoothness, so it has excellent transparency. Therefore, if the deodorant printed layer of the present invention is laminated with a transparent resin layer to form a laminate for a packaging bag, a packaging bag with excellent visibility of the contents can be obtained.
[0022] Hereinafter, each element constituting the odor eliminating printed layer for packaging bags of the present invention will be described in order.
[0023] <Nanozeolite doped with transition metals> The deodorizing printed layer for packaging bags of the present invention contains nano zeolite doped with a transition metal.
[0024] The zeolite contained in the deodorizing printed layer for packaging bags of the present invention may have pores defined by eight-membered rings, and its skeletal structure may be, for example, AEI, AFT, AFX, CHA, DDR, ERI, ITE, ITW, KFI, LEV, LTA, MER, PAU, RHO, UFI, etc.
[0025] The zeolite contained in the deodorant printed layer for packaging bags of the present invention may be a hydrophilic zeolite. The hydrophilicity of zeolite is indicated by the silica-alumina ratio (SAR, SiO2 / Al2O3 molar ratio), and the larger this value is, the higher the hydrophobicity is, and the smaller this value is, the higher the hydrophilicity is. The SAR of the zeolite in the present invention may be 20 or less, 15 or less, 10 or less, 8.0 or less, 5.0 or less, 3.0 or less, or 2.0 or less. There is no lower limit for the SAR, but generally, it is difficult to synthesize a zeolite with a SAR of less than 1. From this viewpoint, the SAR of the zeolite contained in the deodorant printed layer for packaging bags of the present invention may be 0.8 or more, 0.9 or more, or 1.0 or more.
[0026] In addition, in conventional printing methods, the deodorizing agent contained in the ink adsorbs the organic solvent, blocking the adsorption sites for unpleasant odors, and the resulting packaging bag is unable to exhibit the desired deodorizing function, resulting in insufficient deodorizing properties.
[0027] In contrast, when the transition metal-doped zeolite used in the present invention is hydrophilic, it maintains its deodorizing performance without being affected by the organic solvent contained in the normal ink. Therefore, the deodorizing printed layer for packaging bags of this embodiment can be easily formed by a printing method using the ink for forming the deodorizing printed layer described below. Therefore, according to the present invention, a high level of deodorizing performance can be obtained without the need to manufacture a dedicated deodorizing film, and the manufacturing process of the packaging bag including the deodorizing printed layer for packaging bags of the present invention is simplified.
[0028] The zeolite contained in the odor eliminating printed layer for packaging bags of the present invention is doped with a transition metal. The transition metal doped in the zeolite of the present invention may be, for example, V, Cr, Mn, Fe, Co, Ni, Cu, Nb, Mo, Ru, Rh, Pd, Ag, Ce, Zn, etc., and may be one or more selected from Ag, Cu, and Zn.
[0029] The doping amount of the transition metal, relative to the Al atoms contained in the zeolite, may be, for example, 10 mol% or more, 15 mol% or more, 20 mol% or more, 25 mol% or more, 30 mol% or more, 40 mol% or more, 50 mol% or more, or 55 mol% or more, and may be less than 100 mol%, 95 mol% or less, 90 mol% or less, 80 mol% or less, 70 mol% or less, 60 mol% or less, 55 mol% or less, 50 mol% or less, or 45 mol% or less.
[0030] When the transition metal is Ag, the doping amount may be, for example, 20 mol% or more or 25 mol% or more, and, for example, 60 mol% or less or 55 mol% or less, based on the Al atoms contained in the zeolite.When the transition metal is Cu, the doping amount may be, for example, 50 mol% or more or 55 mol% or more, and, for example, less than 100 mol% or 95 mol% or less, based on the Al atoms contained in the zeolite.When the transition metal is Zn, the doping amount may be, for example, 10 mol% or more or 15 mol% or more, and, for example, 50 mol% or less or 45 mol% or less, based on the Al atoms contained in the zeolite.
[0031] Doping of the zeolite with the transition metal may be carried out, for example, by known ion exchange methods.
[0032] The zeolite contained in the deodorant printed layer for packaging bags of the present invention is nano-zeolite with a small particle size. The average particle size of the nano-zeolite may be, for example, 5 nm or more, 10 nm or more, 20 nm or more, 25 nm or more, 30 nm or more, 35 nm or more, or 40 nm or more, and may be, for example, 500 nm or less, 400 nm or less, 300 nm or less, 250 nm or less, 200 nm or less, 150 nm or less, 100 nm or less, or 80 nm or less.
[0033] The above average particle size is a particle size at which the cumulative mass percentage is 50% in the particle size distribution obtained by a laser diffraction method measured in accordance with JIS Z8825:2022.
[0034] The content of zeolite in the deodorizing printed layer for packaging bags of the present invention may be, for example, 10 mass% or more, 15 mass% or more, 20 mass% or more, or 25 mass% or more, based on the total mass of the deodorizing printed layer, and may be, for example, 50 mass% or less, 45 mass% or less, 40 mass% or less, or 35 mass% or less.
[0035] The content of zeolite in the deodorant printed layer is, for example, 0.1 g / m as the mass of zeolite per unit area of the printed layer. 2 More than 0.2g / m 2 or more, or 0.3 g / m 2 or more, for example, 6.0 g / m 2 Below 4.0g / m 2 Below 3.0g / m 2 Below 2.0g / m 2 Below 1.5g / m 2 Below 1.2g / m 2 Below, 0.8g / m 2 or less than 0.5g / m 2 It may be the following:
[0036] <resin> The deodorant printed layer for packaging bags of the present invention contains a resin. The resin has the function of maintaining the layer structure of the deodorant printed layer and dispersing and retaining the transition metal-doped nano zeolite.
[0037] The resin may be one or more selected from, for example, polyurethane resin, (meth)acrylic resin, polyamide resin, nitrocellulose resin, chlorinated polyolefin resin, vinyl chloride-vinyl acetate copolymer resin, and the like.
[0038] The resin content in the deodorizing printed layer for packaging bags of the present invention may be, for example, 50 mass% or more, 55 mass% or more, 60 mass% or more, or 65 mass% or more, based on the total mass of the deodorizing printed layer, and may be, for example, 90 mass% or less, 85 mass% or less, 80 mass% or less, or 75 mass% or less.
[0039] <Optional ingredients> The deodorant printed layer for packaging bags of the present invention contains nano zeolite doped with a transition metal and a resin. The deodorant printed layer may contain optional components other than these. The optional components in the deodorant printed layer may be, for example, a filler, a colorant, a defoamer, an anti-aging agent, etc.
[0040] <Coating amount of deodorizing printing layer for packaging bags> The deodorizing printed layer for packaging bags of the present invention is a deodorizing layer that is thin but has excellent adsorption properties, particularly for sulfur compounds.
[0041] The coating amount of the deodorant printed layer for packaging bags of the present invention is, for example, 0.3 g / m2 as a mass per unit area. 2 More than 0.5g / m 2 More than 0.7g / m 2 or more, or 0.8 g / m 2 or more, for example, 15.0 g / m 2 Below, 12.0g / m 2 Below, 10.0g / m 2 Below 8.0g / m 2 Below 5.0g / m 2 Below 4.0g / m 2 Below 3.0g / m2 Below 2.0g / m 2 Less than or equal to 1.5g / m 2 It may be the following:
[0042] The thickness of the deodorant printed layer for packaging bags of the present invention may be approximately 0.1 μm or more or 1 μm or more, and may be 5 μm or less or 10 μm or less.
[0043] <Ink for forming deodorant printing layer> According to another aspect of the present invention, there is provided an ink for forming a deodorant printed layer.
[0044] The ink for forming a deodorant printed layer of the present invention contains a nanozeolite doped with a transition metal and a resin, and may further contain a solvent and other optional components.
[0045] The ink for forming the deodorant printed layer of the present invention is preferably used to form the deodorant printed layer for packaging bags of the present invention. Therefore, the type of nano zeolite doped with transition metal and the resin contained in the ink for forming the deodorant printed layer of the present invention may be the same as the zeolite and the resin contained in the desired deodorant printed layer for packaging bags. The ratio of the zeolite and the resin in the ink may also be the same as the ratio of the zeolite and the resin in the desired deodorant printed layer.
[0046] The solvent contained in the ink for forming the deodorant printing layer is not particularly limited as long as it can disperse the transition metal-doped nanozeolite and dissolve the resin. The solvent may be, for example, one or more selected from esters, alcohols, ketones, ethers, hydrocarbons, etc.
[0047] Examples of esters include ethyl acetate, n-propyl acetate, isopropyl acetate, n-butyl acetate, isobutyl acetate, and isoamyl acetate; Examples of alcohols include methanol, ethanol, n-propanol, and isopropanol; Examples of ketones include acetone, methyl ethyl ketone, methyl-n-butyl ketone, and methylcyclohexanone; Examples of ethers include diethyl ether, tetrahydrofuran, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, and ethylene glycol monoethyl ether acetate; Examples of hydrocarbons include toluene, xylene, and n-hexane; Examples of each can be given.
[0048] The amount of the solvent may be appropriately determined by those skilled in the art so that the ink has an appropriate viscosity depending on the printing method to be used.
[0049] The optional components contained in the ink for forming the deodorant printed layer of the present invention may be the optional components contained in the desired deodorant printed layer as well as the components contained in the ink. Such optional components may be, for example, a penetrating agent, a drying inhibitor, a pH adjuster, a preservative, etc.
[0050] 《Laminated body for packaging bags》 According to yet another aspect of the present invention, a laminate for a packaging bag is provided.
[0051] The laminate for packaging bags of the present invention includes a substrate layer, the deodorizing printed layer of the present invention, and a sealant layer. This laminate for packaging bags may further include one or two layers selected from a barrier layer and a reinforcing layer.
[0052] The base layer may be made of a material appropriately selected from materials that can exhibit the necessary physical properties when made into a packaging bag, and may be made of one or more materials selected from, for example, polyethylene terephthalate, polypropylene, nylon, paper, aluminum foil, etc.
[0053] The barrier layer has the role of protecting the contents of the packaging bag from the environment outside the bag, and may have the function of blocking, for example, oxygen, moisture, etc. The barrier layer may be made of, for example, aluminum foil, metal-vapor-deposited nylon film, silica-vapor-deposited nylon film, metal-vapor-deposited polyethylene terephthalate film, silica-vapor-deposited polyethylene terephthalate film, etc.
[0054] The reinforcing layer has the role of imparting strength, durability, etc. to the packaging bag. The reinforcing layer may be made of, for example, nylon, oriented polypropylene, polyethylene terephthalate, or the like.
[0055] The sealant layer has a heat-sealing ability, and has the function of forming and maintaining the shape of the packaging bag and sealing the contents. The sealant layer may be made of, for example, polyolefin. When the laminate for packaging bags of the present invention is intended to heat-treat the contents, the sealant layer is preferably made of unstretched polypropylene, which has excellent heat-sealing ability and excellent heat resistance. On the other hand, when the laminate for packaging bags of the present invention is not intended to heat-treat the contents, there is no restriction on the sealant layer in terms of heat resistance, and general polyolefins, such as LDPE, LLDPE, polypropylene, etc., can be used.
[0056] In a laminate for a packaging bag including a substrate layer, a deodorant printed layer, and a sealant layer, the deodorant printed layer may be disposed on the inner side (the side of the contents) of the substrate layer and on the outer side of the sealant layer. Such a laminate for a packaging bag may be manufactured by a method including printing the ink for forming the deodorant printed layer of the present invention on one side of at least one of the substrate layer and the sealant layer.
[0057] Specifically, for example, Printing the ink for forming the deodorant printed layer of the present invention onto a substrate layer; Dry laminating the base layer on which the deodorant printed layer is printed and the sealant layer. Thus, a laminate for packaging bags is manufactured. Here, the deodorant printed layer is disposed so as to be located between the substrate layer and the sealant layer. In addition, printing of the ink for forming the deodorant printed layer on the substrate layer may be performed only once, or printing may be performed twice or more to increase the thickness of the deodorant printed layer.
[0058] An example of a packaging bag laminate produced by this method is shown as a schematic cross-sectional view in Figure 1. The packaging bag laminate (101) in Figure 1 has, in this order, a base layer (10), a deodorant printed layer (20), a laminate adhesive layer (40), and a sealant layer (30).
[0059] In a packaging bag laminate further comprising one or two layers selected from a barrier layer and a reinforcing layer in addition to a substrate layer, a deodorant printed layer, and a sealant layer, the deodorant printed layer may be disposed on the inner side (contents side) of the substrate layer and on the outer side of the sealant layer. Such a packaging bag laminate may be produced by a method including printing the ink for forming the deodorant printed layer of the present invention on one side of at least one layer of the substrate layer, the barrier layer, the reinforcing layer, and the sealant layer.
[0060] In the laminate for packaging bags including the barrier layer, from the viewpoint of effectively exerting the deodorizing function, the deodorizing printed layer may be disposed inside (on the content side) of the barrier layer and outside of the sealant layer. Such a laminate for packaging bags may be manufactured, for example, by a method including printing the ink for forming the deodorizing printed layer of the present invention on the reinforcing layer.
[0061] Specifically, for example, Printing the ink for forming the deodorant printed layer of the present invention onto the reinforcing layer; Dry lamination of the base layer, the barrier layer, the reinforcing layer on which the deodorant printed layer is printed, and the sealant layer in this order. Here, the deodorant printed layer is disposed so as to be located between the reinforcing layer and the sealant layer.
[0062] An example of a packaging bag laminate produced by this method is shown as a schematic cross-sectional view in Figure 2. The packaging bag laminate (102) in Figure 2 has, in this order, a base layer (10), a laminate adhesive layer (40), a barrier layer (11), a laminate adhesive layer (40), a reinforcing layer (12), an odor-eliminating printed layer (20), a laminate adhesive layer (40), and a sealant layer (30).
[0063] In the above, the printing of the deodorant printing layer forming ink may be performed by a method appropriately selected from known printing methods. For example, letterpress printing, gravure printing, offset printing, silk screen printing, inkjet printing, etc. may be used for printing the deodorant printing layer forming ink.
[0064] The dry lamination adhesive used for dry lamination may be appropriately selected from, for example, ester-based, ether-based, etc. Since the laminate for packaging bags of the present invention is premised on heat treatment of the contents, a two-liquid ester-based adhesive having excellent heat resistance is preferable as the dry lamination adhesive.
[0065] The laminate for packaging bags of the present invention can deodorize odors, particularly sulfur odors, emanating from the contents or the packaging bag, or both, when the laminate is heat-treated in a state in which the contents are sealed as a packaging bag. Therefore, the laminate for packaging bags of the present invention can be suitably applied to, for example, packaging bags for retort foods. Examples of retort foods include porridge, side dishes, nursing care foods, baby foods, etc.
[0066] The laminate for packaging bags of the present invention can also be used as a packaging bag for products that have a problem with the unpleasant odor that the substance itself has even without heating. Examples of such products include medicines, supplements, etc. Examples of medicines and supplements include vitamins, amino acid preparations, DHA / EPA-based preparations, garlic-based preparations, etc.
[0067] The laminate for packaging bags of the present invention can also be used as storage bags (such as laminate packs) for electrical and electronic devices that may be affected by outgassing (especially sulfur-based gases). Examples of such products include sulfide-based all-solid-state batteries. EXAMPLES
[0068] In the following Examples and Comparative Examples, the following materials were used as the inks and the laminate for packaging bags.
[0069] Ink raw materials <Zeolite> Abscents 3000: Product name, high silica zeolite manufactured by Resonac Universal Co., Ltd., SAR=3,000, MFI type, average particle size 3-5μm (3,000-5,000nm) Nano ZSM-5: Crushed ZSM-5, SAR>20, MFI type, average particle size 50nm 4A: Na-A type zeolite, SAR=1, LTA type, average particle size 3-5μm (3,000-5,000nm) Zeoal-4A: Na-A type zeolite, SAR=1, LTA type, average particle size 50nm
[0070] <Transition metal doped zeolite> Zeoal-Ag: Nakamura Choukou Co., Ltd., "Zeoal (registered trademark) Ag", Ag-nano zeolite, Na-A type zeolite + 30-50 mol% of the ions are Ag + Ion-exchanged zeolite, SAR=1, LTA type, average particle size 50 nm Zeoal-Cu: Nakamura Choukou Co., Ltd., "Zeoal (registered trademark) Cu", Cu-nano zeolite, Na-A type zeolite + 60-90 mol% of the ions are Cu 2+ Ion-exchanged zeolite, SAR=1, LTA type, average particle size 50 nm Zeoal-Zn: Nakamura Choukou Co., Ltd., "Zeoal (registered trademark) Zn", Zn-nano zeolite, Na-A type zeolite + 20-40 mol% of the ions are Zn 2+ Ion-exchanged zeolite, SAR=1, LTA type, average particle size 50 nm
[0071] The above average particle size is a particle size at which the cumulative mass percentage is 50% in the particle size distribution obtained by a laser diffraction method measured in accordance with JIS Z8825:2022.
[0072] <Resin component> Rio Alpha SX R Medium: Trade name, manufactured by Toyo Ink Co., Ltd., a medium containing polyurethane resin and solvent.
[0073] 《Laminated material raw material for packaging bags》 <Base material layer> PET(12): Polyethylene terephthalate film, thickness 12 μm
[0074] <Barrier layer> AL(9): Aluminum foil, thickness 9 μm
[0075] <Reinforcing layer> Ny(15): Nylon film, thickness 15 μm,
[0076] <Sealant layer> CPP(50): Unstretched polypropylene film, thickness 50μm
[0077] <Laminating adhesive> Mitsui Chemicals' two-component ester adhesive Main ingredient: Takelac (registered trademark) A-525 Hardener: Takenate (registered trademark) A-52
[0078] Example 1 (1) Preparation of ink for forming deodorant printing layer 100 parts by mass of Rio Alpha SX R medium, 40 parts by mass of ethyl acetate, 20 parts by mass of isopropanol, and 20 parts by mass of methyl ethyl ketone as dilution solvents, and 7.0 parts by mass of Zeoal-Ag as a deodorant (zeolite) were mixed and thoroughly stirred to prepare an ink for forming a deodorant print layer. The content of the deodorant (zeolite) in the obtained ink was 3.7% by mass.
[0079] (2) Formation of deodorant printing layer The ink for forming the deodorant printing layer obtained above was printed on one side of the Ny (15) as a reinforcing layer, and the coating amount after drying was 1.0 g / m 2 (Deodorant amount: 0.32g / m 2 ) was formed as a deodorizing printed layer.
[0080] The printability of this printing was evaluated according to the following criteria. A: When the printing layer was smooth C: When the printing layer is not smooth
[0081] (3) Formation of laminate for packaging bag Using the Ny(15) obtained above after printing with the ink for forming the deodorant printed layer, a laminate for a packaging bag having the following configuration was produced by a dry lamination method. PET(12) / / AL(9) / / Ny(15) / Deodorizing printing layer / / CPP(50)
[0082] Here, " / / " indicates a layer of laminating adhesive in dry lamination. Ny (15) was used with the deodorant printed layer facing the CPP (50).
[0083] (4) Evaluation The laminate for packaging bags obtained above was used to heat-seal the ends to form a packaging bag with an inner dimension of 100 mm x 40 mm. 10 mL of an L-cysteine aqueous solution with a concentration of 300 ppm was sealed inside the packaging bag. The packaging bag after sealing was placed in a thermostatic chamber and heated at 120°C for 30 minutes. The hydrogen sulfide concentration in the L-cysteine aqueous solution after heating was measured and a sensory test for sulfur odor was performed using the following methods.
[0084] (i) Measurement of hydrogen sulfide concentration The hydrogen sulfide concentration in the L-cysteine aqueous solution after heating was measured using a simple water quality measuring device, "Pack Test Sulfide (Hydrogen Sulfide) WAK-S" manufactured by Kyoritsu Chemical Research Institute Co., Ltd.
[0085] (ii) Sensory test for sulfur odor After heating, the packaging bag was opened, and immediately after opening, panelists (evaluators) checked whether or not there was a sulfur odor in the packaging bag, and rated it on the following three-level scale. A: Has a sulfur smell B: Slight sulfur smell C: No sulfur smell
[0086] The number of panelists was five, and the result presented by the largest number of panelists was adopted as the evaluation result.
[0087] Examples 2 and 3, and Comparative Examples 1 to 5 Except for using the zeolite listed in Table 1, the ink for forming the deodorant printed layer was prepared in the same manner as in Example 1, and a laminate for packaging bags was formed and evaluated using the ink. In Comparative Example 1, a laminate for packaging bags was produced and evaluated without printing the ink for forming the deodorant printed layer on Ny(15).
[0088] The above results are summarized in Table 1.
[0089] [Table 1]
[0090] Referring to Table 1, the following can be seen:
[0091] The laminates of Comparative Examples 2 and 3, which contain a deodorizing printed layer formed using a hydrophobic zeolite with an SAR of more than 20 as a deodorizing agent, did not show any effect in reducing hydrogen sulfide concentration and sulfur odor compared to the laminate of Comparative Example 1, which did not have a deodorizing printed layer.
[0092] In addition, the laminates of Comparative Examples 4 and 5, which include a deodorizing printed layer formed using hydrophilic zeolite with an SAR of 20 or less but not doped with a transition metal, did not show any effect in reducing hydrogen sulfide concentration and sulfur odor compared to the laminate of Comparative Example 1.
[0093] Furthermore, the inks for forming deodorant printed layers in Comparative Examples 2 and 5, which were prepared using zeolite with a large dispersed particle size, formed deodorant printed layers with insufficient smoothness.
[0094] In contrast, the laminates of Examples 1 to 3, which include a deodorant printed layer formed using hydrophilic zeolite with an SAR of 20 or less and doped with a transition metal, had a significant effect of reducing the hydrogen sulfide concentration and sulfur odor compared to the laminate of Comparative Example 1. Furthermore, in Examples 1 to 3, nano-zeolite with a small dispersed particle size was used, and the ink for forming the deodorant layer containing this had excellent printability, and the formed deodorant printed layer had high smoothness. [Explanation of symbols]
[0095] 10 Base material layer 11 Barrier layer 12 Reinforcement layer 20 Deodorizing printed layer 30 Sealant Layer 40 Laminating adhesive layer 101, 102 Laminate for packaging bags
Claims
1. The present invention relates to a method for producing a nano-zeolite composition comprising: Coating amount: 15.0 g / m 2 Below is the Deodorizing printing layer for packaging bags.
2. The deodorizing printed layer according to claim 1 , wherein the average particle size of the nano zeolite is 5 nm or more and 500 nm or less.
3. The deodorizing printed layer according to claim 1 , wherein the nano zeolite has an SAR of 20 or less.
4. The deodorizing printed layer according to claim 2 , wherein the SAR of the nano zeolite is 20 or less.
5. The deodorant printed layer according to claim 1 , wherein the transition metal is one or more selected from Ag, Cu, and Zn.
6. The deodorizing printed layer according to claim 1, wherein the resin is one or more selected from urethane resin, (meth)acrylic resin, polyamide resin, nitrocellulose resin, chlorinated polyolefin resin, and vinyl chloride-vinyl acetate copolymer resin.
7. An ink for forming an odor-eliminating printing layer, comprising a nano-zeolite doped with a transition metal and a resin.
8. The ink for forming a deodorant printed layer according to claim 7, which is used to form the deodorant printed layer according to claim 1.
9. A laminate for a packaging bag, comprising a substrate layer, the deodorizing printed layer according to claim 1, and a sealant layer.
10. The laminate for packaging bags according to claim 9, further comprising one or two layers selected from a barrier layer and a reinforcing layer.
11. A method for producing the packaging bag laminate according to claim 9, printing the ink according to claim 7 onto at least one of the substrate layer and the sealant layer; A method for manufacturing a laminate for a packaging bag.
12. A method for producing the packaging bag laminate according to claim 10, 8. A method for producing a laminated laminated laminate comprising: printing the ink of claim 7 onto at least one of the substrate layer, the barrier layer, the reinforcing layer, and the sealant layer. A method for manufacturing a laminate for a packaging bag.
Citation Information
Patent Citations
Packaging material
JP2015027892A
Laminate for heat sterilization treatment, packaging material for heat sterilization treatment and package for heat sterilization treatment
JP2019177518A
Gravure ink composition for adsorbing sulfur-based compound, sulfur-based compound adsorption printed matter, laminate, method for manufacturing sulfur-based compound adsorption printed matter, method for manufacturing laminate, packaging bag, and packaging container
JP2022099681A